Competition between hybrid derivatives and borrowings - Inčiuraitė-Noreikienė, Lina (Baltistica, 2022)
This article introduces the patterns of competing hybrid and correlative derivatives and borrowings, discusses their formation and frequency of use based on the data extracted from the Corpus of the Contemporary Lithuanian Language. The research has revealed that competition occurs between 1) hybrid suffixed derivatives (debatuo-toj-as, -a / debat-inink-as, -ė ‘debater’), 2) hybrid and correlative suffixed derivatives (legion-inink-as, -ė / legion-ier-ius, -ė ‘legionnaire’), 3) hybrid suffixed derivatives and borrowings (akrobat-inink-as, -ė / akrobat-as, -ė ‘acrobat’). Competing nouns can belong either to the same or distinct derivational category. They can also be derived either from the same or different base words. A large difference in the frequency of use can be seen in the hybrid derivatives (debatuotojas, -a ×119 / debatininkas, -ė ×5 ‘debater’), in the hybrid and correlative derivatives (propagandininkas, -ė ×58 / propagandistas, -ė ×152 ‘propagandist’), in the hybrid derivatives and borrowings (akrobatininkas, -ė ×2 / akrobatas, -ė ×289 ‘acrobat’). The same frequency of use can be seen in the hybrid derivatives with different suffixes (sabotuotojas, -a ×16 / sabotažininkas, -ė ×16 ‘saboteur’).